Pengaruh Digital Marketing, Cita Rasa, dan Promosi Terhadap Keputusan Pembelian di Mie Ayam dan Bakso 45 Burengan Kota Kediri - Febby Fauzi Hermanto; Ustadus Sholihin; Zaenul Muttaqien (Jurnal Nuansa : Publikasi Ilmu Manajemen dan Ekonomi Syariah, 2025)
This study aims to determine the influence of Digital Marketing, Taste and Promotion variables on Purchasing Decisions at Mi Ayam and Bakso 45 Burengan. This type of research is quantitative research. The data for this study were obtained through questionnaires, interviews, and literature studies. The analysis techniques used were Validity Test, Reliability Test, Classical Assumption Test, Multiple Linear Regression Analysis, t-test, F-test and Determination Coefficient Test. The results of the t-test of the digital marketing, taste and promotion variables had a significant partial effect on purchasing decisions with sig <0.05. The results of the F test can be concluded that digital marketing, taste and promotion have a simultaneous and significant effect on Purchasing Decisions at Mi Ayam and Bakso 45 Burengan with sig. <0.05.